Job scheduling strategies for parallel processing : 18th International Workshop, JSSPP 2014, Phoenix, AZ, USA, May 23, 2014. Revised selected papers /: 18th International Workshop, JSSPP 2014, Phoenix, AZ, USA, May 23, 2014. Revised selected papers. (2015) - Unknown
No abstract available